Embolization for Perimedullary Arteriovenous Fistulae: Pioneering Experience in Peru - R. Plasencia, Andrés; G. Solís, Frank; Santillán, Alejandro (Journal of Neurological Research And Therapy, 2021)
Background Perimedullary arteriovenous fistulae, or type IV spinal cord arteriovenous malformations, are very rare and not well-known lesions. This paper aims to present our endovascular experience with these lesions. Methods We report our experience with 4 patients with perimedullary arteriovenous fistulae, subtypes b and c (macrofistulae), exhibiting severe neurological impairment. The patients were treated with endovascular embolization. Results Complete fistula eradication was achieved in all of them. One complication occurred. We discuss the natural history, pathophysiology, clinical presentation, prognosis and embolization techniques, along with the angiographic and clinical outcomes. Conclusion Our experience with endovascular embolization as an upfront treatment allowed us to eradicate these lesions in a safe and effective way, arresting the clinical worsening and reversing partially or completely the neurological injury in most of our cases.
Keywords: Perimedullary; Arteriovenous fistula; Spinal Cord; Embolization; AVM